Assessing the sustainability of grass-based livestock husbandry in Hulun Buir, China. (December 2020) - Zhao, Zhe; Chen, Jiancheng; Bai, Yuping; Wang, Pei
Abstract : Recently, affected by the changes of dietary structure and the deterioration of ecological environment, expanding the output of livestock products within the carrying capacity of grassland resources has become a major strategic demand of the country. Achieving sustainable development of grass-based livestock husbandry is of great significance for ensuring the ecological security of grassland and national food security, but there is still short of sustainable development pattern for reference. To further refine a sustainable pattern, an "Eco-engineering Experimental Area" (Experimental Area) was established in Hulun Buir, taking pastures as basic production unit and carrying out the "grain - cash - forage" three-dimensional planting structure, but the rest of the region still belongs to traditional development pattern. In this paper, we applied Emergy Analysis to unify the different sacle of grass-based livestock husbandry into comparable production units, and assess the sustainability of grass-based livestock husbandry in the Experimental Area and the traditional pastoral area of Hulun Buir. The results showed that the Energy-based Sustainability Index (ESI) of Experimental Area was much higher than the traditional pastoral area, indicating that the "grain - cash - forage" three-dimensional planting structure in Experimental Area supported by artificial forage has higher sustainable development potential and economic development potential than traditional development pattern. Enhancing technology, as well as changing the production management mode and increasing the yield of high-quality forage are all helpful to achieve sustainable development. Highlights: A emergy evaluation indexwas built from both economic and ecological perspective. The structure of "grain - cash - forage" has higher sustainable development ability. Artificial forage is the key factor to grass-based livestock husbandry.